Effect of Papaya Juice on Constipation in Pregnant Women: Quasi-Experimental Study - Chairiyah, Royani; Wiratmo, Puji Astuti (Journal of Nursing and Midwifery Sciences, 2025)
Constipation is a condition often found in pregnant women that has an impact on physical, psychological, and social disorders such as discomfort, hemorrhoids, disturbed body image, and decreased quality of life. Papaya is highly recommended for pregnant women as a non-pharmacological therapy to treat constipation. The aim of the research was to determine the effect of papaya juice on constipation in pregnant women. Method: This type of quantitative research is a pretest-posttest quasi-experimental design. In the intervention group, 35 pregnant women received papaya juice therapy, while 35 pregnant women in the control group received therapy by drinking warm water. Bivariate analysis with an independent T test and a paired T test The results showed that there was a significant difference in the mean posttest constipation score between the intervention group and the control group (p = 0.001), the average pretest and posttest constipation score in the intervention group (p<0.001), and the average pretest and posttest constipation score in the control group (p<0.001). The decrease in the average constipation score of pregnant women in the intervention group after being given papaya juice was 0.2 (5.71%) lower than the average constipation score of pregnant women in the control group after being given warm water, which was 0.62 (17.14%). Conclusion: Papaya juice is efficacious in reducing symptoms of constipation in pregnant women. Midwives are expected to provide health education on how to prevent constipation by consuming more fruit and vegetables and doing enough activity during pregnancy